The Relevance of Aboriginal Peer-Led Parent Support: Strengthening the Child Environment in Remote Areas - Munns, Ailsa; Walker, R. (2018)
© 2018, © 2018 Taylor & Francis. This participatory action research study was situated within a larger research study, which investigated the development of a peer-led Aboriginal parent support program in the remote setting of Halls Creek in Western Australia. The aim of this smaller research component was to explore the self-perceived role of home visiting peer support workers in this remote area. Participatory Action Research methodology was employed, within which eleven Action Learning Sets were used to facilitate participant collaboration (n = 8). All participant data was collected in focus groups during the Action Learning Sets where culturally appropriate home visiting parent support strategies were developed and examined in partnership with a child health nurse researcher. Data were analyzed using thematic analysis with three themes relating to the peer support workers’ self-perceived role being identified: Helping parents be strong for their children; Strengthening culture; and Facilitating effective communication. These elements support peer support worker activities, helping parents to enhance their children’s physical and psychosocial developmental environment. This research highlights the critical emerging role of peer support workers in home visiting family support in a remote area of Australia.